Maintaining social care provision in the context of financial austerity - Chotvijit, Sarunkorn; Thiarai, Malkiat; Jarvis, Stephen A (International Journal of Population Data Science, 2018)
There is significant national interest in tackling issues surrounding the needs of vulnerable children and adults. At the same time, UK cities are under significant financial strain, as local government financial settlements (the distribution of central government resources) decrease in real terms and yet urban populations, which draw on local government services, continue to grow. This study focusses on the city of Birmingham, the UK’s largest and most populous city outside of London. In a data-led study, using data derived from personal social care records, we analyse the management and delivery of social care services by Birmingham City Council, which itself is the largest local authority in Europe. This research employs state-of-the-art data analytic techniques to analyse six years of Birmingham City Council social care data, to identify: (i) Service cost profiles over time; (ii) Geographic dimensions to service demand and delivery; (iii) Patterns in the provision of services, which may assist with future service planning and provision, and (iv) The extent to which data value and data protection interact. In response to recent fiscal challenges, Birmingham City Council is expected to make savings of £815 million over the 9-year period 2011/12 to 2019/20. Delivering savings of this scale, whilst protecting and safeguarding the most vulnerable citizens within a growing urban population, is one of the biggest challenges facing the UK’s second largest city.